2022
DOI: 10.1136/thoraxjnl-2022-218772
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioleiomyomatosis (LAM) Cell Atlas

Abstract: Lymphangioleiomyomatosis (LAM) is a rare lung disease of women, causing cystic remodelling of the lung and progressive respiratory failure. The cellular composition, microenvironment and cellular interactions within the LAM lesion remain unclear. To facilitate data sharing and collaborative LAM research, we performed an integrative analysis of single-cell data compiled from lung, uterus and kidney of patients with LAM from three research centres and developed an LAM Cell Atlas (LCA) Web-Portal. The LCA offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…To determine the presence of senescent cells in LAM lung tissue, we initially examined gene expression of two canonical senescence markers, the cyclin dependent kinase (CDK) inhibitors CDKN1A (p21) and CDKN2A (p16), using the LAM cell atlas, an open-source data interface comprising single cell RNA sequencing data from 13 lung samples 24 . p21 was ubiquitously expressed throughout the LAM lung including in TSC null LAM core cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the presence of senescent cells in LAM lung tissue, we initially examined gene expression of two canonical senescence markers, the cyclin dependent kinase (CDK) inhibitors CDKN1A (p21) and CDKN2A (p16), using the LAM cell atlas, an open-source data interface comprising single cell RNA sequencing data from 13 lung samples 24 . p21 was ubiquitously expressed throughout the LAM lung including in TSC null LAM core cells.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Single cell RNA sequencing of LAM lung tissues showing expression of p16 and p21 in LAM lung populations using the LAM cell atlas 24 . Left panels show expression of positive cells for p21 and p16 in each cluster, right panels show the fold change and significance for LAM compared with control lung.…”
Section: Resultsmentioning
confidence: 99%
“…In sum, these studies suggest that both cells of uterine and lung mesenchyme origin may be involved in the development of LAM -perhaps the former comprise the core smooth muscle cell-like LAM tumor cells, while the latter are responsible for the cystic lung disease. More studies that include use of a newly developed LAM Cell Atlas (Du et al 2023) will help clarify these questions.…”
Section: Origin and Nature Of Lam Cellsmentioning
confidence: 99%
“…Characterization of the human LAM tumor immune microenvironment is nascent, and the myeloid content of LAM lesions is understudied. The LAM Cell Atlas (Du et al 2023) has identified various immune cell populations in the LAM lung, including tumor-perturbed neutrophils (Minor et al 2023), as well as inflammatory macrophage and monocyte populations, conventional and plasmacytoid dendritic cells, and other granulocytes such as mast cells and basophils. While a few studies have suggested a potential role for macrophages and monocytes in the immune-suppressive LAM tumor immune microenvironment, as mentioned above, only mast cells and neutrophils have been assessed by functional assay, leaving much to be illuminated about the significance of the diverse myeloid compartment of the LAM tumor immune microenvironment.…”
Section: The Immune Microenvironment and Lammentioning
confidence: 99%
“…A publicly available LAM cell atlas has been constructed using single-cell RNA sequencing LAM lung data from three research groups. This resource allows for convenient exploration of the transcriptome of the LAM lung ( https://research.cchmc.org/pbge/lunggens/LCA/LCA.html ) [ 8 ].…”
Section: Introduction To Lymphangioleiomyomatosismentioning
confidence: 99%